Exploring RNA modifications, editing, and splicing changes in hyperuricemia and gout - Huang, Chung-Ming; Chen, Yu-Chia; Lai, I-Lu; Chen, Hong-Da; Huang, Po-Hao; Tu, Siang-Jyun; Lee, Ya-Ting; Yen, Ju-Chen; Lin, Chia-Li; Liu, Ting-Yuan; Chang, Jan-Gowth (Frontiers in Medicine, 2022)
Hyperuricemia and gout are two of the most common metabolic disorders worldwide; their incidence is increasing with changes in lifestyle, and they are correlated with many diseases, including renal and cardiovascular diseases. The majority of studies on hyperuricemia and gout have focused on the discovery of the associated genes and their functions and on the roles of monocytes and neutrophils in the development of gout. Virtually no studies investigating the epigenomics of gout disease or exploring the clinical significance of such research have been conducted. In this study, we observed that the expression of enzymes involved in RNA modifications or RNA editing was affected in UA- or MSU-treated cell lines. RNA alternative splicing and splicing factors were also affected by UA or MSU treatment. We used transcriptome sequencing to analyze genome-wide RNA splicing and RNA editing and found significant changes in RNA splicing and RNA editing in MSU- or UA-treated THP-1 and HEK293 cells. We further found significant changes of RNA modifications, editing, and splicing in patients with gout. The data indicate that RNA modifications, editing, and splicing play roles in gout. The findings of this study may help to understand the mechanism of RNA splicing and modifications in gout, facilitating the development of new diagnostic and therapeutic strategies.